Qualitative analysis of cancer care experiences among rural cancer survivors and caregivers. Issue 4 (5th April 2022) - Ratnapradipa, Kendra L.; Ranta, Jordan; Napit, Krishtee; Luma, Lady Beverly; Robinson, Tamara; Dinkel, Danae; Schabloske, Laura; Watanabe‐Galloway, Shinobu
Abstract: Purpose: Rural (vs urban) patients experience poorer cancer outcomes and are less likely to be engaged in cancer prevention, such as screening. As part of a community needs assessment, we explored rural cancer survivors' and caregivers' experiences, perceptions, and attitudes toward cancer care services. Methods: We conducted 3 focus groups (N = 20) in Spring 2021 in rural Nebraska. Findings: Three patterns of cancer diagnosis were regular care/screening without noticeable symptoms, treatment for symptoms not initially identified as cancer related, and symptom self‐identification. Most participants, regardless of how diagnosis was made, had positive experiences with timely referral for testing (imaging and biopsy) and specialist care. Physician interpersonal skills set the tone for patient‐provider communication, which colored the perception of overall care. Participants with physicians and care teams that were perceived as "considerate, " "compassionate, " and "caring" had positive experiences. Participants identified specific obstacles to care, including financial barriers, transportation, and lack of support groups, as well as more general cultural barriers. Survivors and caregivers identified organization‐based supports that helped them address such barriers. Conclusions: Rural populations have unique perspectives about cancer care. Our results are being used by the state cancer coalition, state cancer control program, and the National Cancer Institute‐designated cancer center to prioritize outreach and interventions aimed to reduce rural cancer disparities, such as revitalizing lay cancer navigator programs, conducting webinars for primary care and cancer specialty providers to discuss these findings and identify potential interventions, and collaborating with national and regional cancer support organizations to expand reach in rural communities.